Health insurance coverage and out-of pocket expenditure: A study among rural and urban households of Faridabad, Haryana - Mitasha Singh; Pooja Goyal; Sangeeta Narang; Abhishek Singh; Mansi Singal (Wolters Kluwer Medknow Publications, 2022)
Introduction: Catastrophic health spending is one of the major factors pushing people into poverty. Reducing "out-of-pocket expenditure (OOPE)" on health through health insurance coverage is an effective approach. The objectives of this study are (1) to estimate health insurance coverage among rural and urban households (HHs) and (2) to determine the proportion of income spent on health as OOPE among the selected HHs. Material and Methods: A cross-sectional study was conducted in rural and urban parts of district Faridabad, Haryana. A sample of 374 were taken from rural and urban areas. The unit of the study was HHs in both the areas. The proportion of income spent on health care (both direct and indirect expenses included) as OOPE was taken as outcome variable. Results: Health insurance coverage was higher among urban HHs (58.0%) as compared to the rural (38.5%). The rural population was availing of private consultation, laboratory, and pharmacy services to a greater extent than the urban; hence, they were spending a substantial proportion of their income on health-care services. The majority of the HHs in the rural and urban areas spent up to 20% of their income on health care. Conclusion: Universal health coverage without health insurance is unlikely.